Android security internals : an in-depth guide to Android's security architecture - Elenkov, Nikolay (USA Nikolay Elenkov, 2020)
"There are more than one billion Android devices in use today, each one a potential target. Unfortunately, many fundamental Android security features have been little more than a black box to all but the most elite security professionals until now. In Android Security Internals, top Android security expert Nikolay Elenkov takes us under the hood of the Android security system. Elenkov describes Android security architecture from the bottom up, delving into the implementation of major security related components and subsystems, like Binder IPC, permissions, cryptographic providers, and device administration."--Publisher's website.
includes index
Keywords: Operating systems (Computers) -- Security measures; Mobile computing -- Security measures; Smartphones -- Security measures; Smartphones -- Design and construction; Smartphones -- Programming